Assessment of environmental laws in Bangladesh: a GIS based case study on brickfields of Savar - Bhuiyan, Md. Masudur Rahman (BRAC University, 2014)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2013.